Will the Middle East implode? By Mohammed Ayoob. Cambridge: Polity Press, 2014, pp. 192, ISBN: 978-0-7456-7924-2 - Shukri, Syaza Farhana Mohamad (IIUM Press, International Islamic University Malaysia, 2015)
As the title implies, Will the Middle East Implode? is a book written by renowned scholar on the Middle East, Mohammed Ayoob, to answer the question on the future of one of the most volatile regions in the world. The future of the Middle East is more unpredictable now than ever following the Arab Spring which shook the world in 2011. Rather than adding to the growing body of work trying to analyse the Arab Spring in a wider theoretical framework, this book gives an important overview of the current situation that some may overlook and what the author believes to be the eventual outcome. The author argues that, “given these interconnections and overlaps [among conflicts], there appears to be a serious danger of a chain reaction developing and leading to an implosion, or a number of mini-implosions, that could engulf much of the region” (p. 4). After the euphoria felt by proponents of democracy in 2012, the author is now pessimistic of the prospect of a new order finally replacing the authoritarian regimes in the Arab world. Ayoob based his arguments mostly on his own expertise on the area and on previous literature covering a wide range of topics regarding the political situation in the Middle East.